Research and Development: A Review of Literature - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1999)
R&D is crucial in a country's development process. Yet some economic agents are hesitant in pursing it not only because of the risks and costs associated with it but also because of high incidence of spillover, which are usually difficult to appropriate. Hence, to mobilize the R&D activities, government interventions are critically needed. This paper reviews issues related to R&D such as the low level of R&D in the Philippines and the opportunity costs associated with it. This also puts into perspective the historical development in S&T and the current policy measures and objectives, the level of S&T, the intensity of R&D activities, the incomplete market structure in research and the government's role through subsidies and incentive provision. This review draws heavily s on the available domestic and international literature on R&D and S&T.
Keywords: 330; science and technology; rate of return; total factor productivity